The impact of KRAS mutations on risk of venous thromboembolism recurrence in patients with metastatic colorectal cancer - Zhikun Liang; Xiaoyan Huang; Jieling Mao; Jingwen Xie; Xiaoyan Li; Li Qin (BMC Gastroenterology)
Abstract Background The relationship between KRAS mutations and the risk of venous thromboembolism (VTE) recurrence in metastatic colorectal cancer (mCRC) patients with established cancer-associated thrombosis (CAT) remains uncertain. This study aims to (1) evaluate the predictive value of seven KRAS mutation subtypes for VTE recurrence and (2) assess the impact of incorporating these mutations into two existing VTE risk scores: the Khorana score and the Ottawa score. Methods Between 2019 and 2023, we identified patients with histologically confirmed mCRC who had symptomatic or incidental index VTE and received anticoagulation therapy. Regression analyses were conducted to calculate hazard ratios (HRs) for recurrent VTE associated with the seven KRAS mutation subtypes. We used receiver operating characteristic (ROC) curves to assess the performance of both the original scores and the modified scores that included KRAS mutations. To quantify the improvements of the modified scores, we calculated the net reclassification improvement (NRI). Results A total of 2,195 patients were enrolled. KRAS G12C, KRAS G12A, and KRAS G13D mutations were significantly associated with a higher risk of recurrent VTE compared to other subtypes, with HRs of 1.84 (95% CI: 1.09–2.97), 2.02 (95% CI: 1.07–3.79), and 1.55 (95% CI: 1.02–2.27), respectively. The original Khorana and Ottawa scores demonstrated moderate predictive ability for VTE recurrence, each with an area under the ROC curve (ROC-AUC) of 0.56 (95% CI: 0.52–0.60). Incorporating the KRAS G12C, KRAS G12A, and KRAS G13D mutations improved the AUCs to 0.70 (95% CI: 0.67–0.74) for the modified Khorana score and 0.71 (95% CI: 0.67–0.74) for the modified Ottawa score. After dichotomizing risk using thresholds from ROC analysis, the NRI values were 0.54 (95% CI: 0.43–0.65) for the modified Khorana score and 0.48 (95% CI: 0.37–0.60) for the modified Ottawa score. Conclusions The KRAS G12C, KRAS G12A, and KRAS G13D mutations are significantly associated with an increased risk of recurrent VTE. Incorporating these specific KRAS mutations into existing risk scores may enhance their predictive accuracy for recurrent VTE in patients with mCRC.